2018
DOI: 10.1038/s41388-018-0537-0
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression-mediated activation of MET in the Golgi promotes HER3/ERBB3 phosphorylation

Abstract: Ligand-dependent oligomerization of receptor tyrosine kinases (RTKs) results in their activation through highly specific conformational changes in the extracellular and intracellular receptor domains. These conformational changes are unique for each RTK sub-family, limiting cross-activation between unrelated RTKs. The proto-oncogene MET receptor tyrosine kinase overcomes these structural constraints and phosphorylates unrelated RTKs in numerous cancer cell lines. The molecular basis for these interactions is u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 68 publications
1
21
0
Order By: Relevance
“…This requires palmitoylation of its cysteine residues for migration to the lipid rafts, where it can activate the TBK1-IRF3 pathway [51]. MET tyrosine kinase is activated and palmitoylated on its extracellular domain at the Golgi [69, 70], and lipid rafts contribute to receptor distribution and stability [70, 71]. These studies raise the interesting possibility that incorporation of KIT into the lipid rafts of the Golgi is involved in protein acylation.…”
Section: Discussionmentioning
confidence: 99%
“…This requires palmitoylation of its cysteine residues for migration to the lipid rafts, where it can activate the TBK1-IRF3 pathway [51]. MET tyrosine kinase is activated and palmitoylated on its extracellular domain at the Golgi [69, 70], and lipid rafts contribute to receptor distribution and stability [70, 71]. These studies raise the interesting possibility that incorporation of KIT into the lipid rafts of the Golgi is involved in protein acylation.…”
Section: Discussionmentioning
confidence: 99%
“…ErbB3 is subject to significantly slower rates of endocytosis than EGF-bound EGFR due to the anti-internalization regions within the C-terminus, allowing for longer periods of receptor activation (when in a heterodimer) [71,112] . This delayed trafficking results in perinuclear accumulation, thereby allowing nuclear localization via retrotranslocation [113] . Once in the nucleus, ErbB3 presents in an activated, uncleaved format, capable of associating with the Cyclin D1 promoter to drive cell proliferation, similar to the mechanism seen in EGFR [54,56,114] .…”
Section: Erbb3 Receptormentioning
confidence: 99%
“…The crystal structure of CDX-3379 binding to HER3 has been solved, which revealed that it binds HER3 outside of the NRG-ligand binding domain and locks HER3 in its auto-inhibited configuration, making the HER3 incapable of binding ligand or dimerizing with other receptors 26,40 . These findings suggest that CDX-3379 may inhibit HER3 via two distinct primary mechanisms of action, liganddependent (i.e., NRG-driven HER3 activation) and ligandindependent (i.e., activation driven by high activity of EGFR, HER2, or multiple other tyrosine kinases 41 ). The Fc portion of CDX-3379 was engineered to enhance binding to the neonatal Fc receptor (FcRN) and thus enhancing its serum half-life in patients and target exposure.…”
Section: Discussionmentioning
confidence: 95%